A4NH flagship 3: Food safety - International Food Policy Research Institute (International Food Policy Research Institute, 2017)
Food safety is moving rapidly up the development agenda as major new studies reveal its severely under-estimated importance. Foodborne disease is responsible for an enormous health burden and negative livelihood, nutritional, and economic impacts. Solutions that are effective in developed countries and export systems have not translated well to informal or formalizing markets. There is an urgent need for technical and institutional solutions to food safety challenges, and broader policy and regulatory approaches to manage food safety risks in dynamic, developing markets.